Avaliação do perfil químico do solo na produtividade da soja (Glycine max) através de mapas de colheita - Lorençon, Jonas (2014)
Agribusiness as a whole has evolved along with the global modernization. Precision Agriculture (PA) is a technology that has been adding in yield of major crops such as soybeans, corn, wheat and coffee. The generation of yield maps and maps of fertility are likely to generate information to make further interventions or remedial applications in crops. Aiming to investigate the relationship between yield maps of soybean with chemical indicators of soil fertility work was undertaken on the property of Seeds Bee the municipality of Coxilha - RS. The study began in 2005 until 2013 in the collection of data on productivity done through maps worked with the aid of Ag Leader SMS software, totaling 5 maps of soybean. The yield maps are generated from information collected in the harvest product. These figures are achieved with devices equipped with GPS, humidity sensor and productivity throughout the harvest generate localized information. From this, the maps was unified into one with three classifications of production zones: high, medium and low. With information from areas of high and low production soil samples were collected up to 1 m deep by 5 points geo-referenced each distinct zone (high and low). In the evaluations of the analysis it was realized that the pH and base saturation and sulfur were the attributes that have higher productivity in relation to depth. The match had a positive influence on productivity up to 0.20 m depth. Organic matter showed no similarities with productivity. In view of this correlation with the factors that influence the production allow the producer a decision which product to apply and how much more needs to be based on georeferenced data from your area. This achieves - rational use of natural resources and therefore the environment can still raise productive crops ceilings.